Using aluminum and Li2CO3 particles to reinforce the alpha-LiAlO2 matrix for molten carbonate fuel cells - Kim, Jin-Eok; Patil, Kailash Yashvant; Han, Jonghee; Yoon, Sung-Pil; Nam, Suk-Woo; Lim, Tae-Hoon; Hong, Seong-Ahn; Kim, Hansung; Lim, Hee-Chun (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
The electrolyte substrate (matrix) of a molten carbonate fuel cell (MCFC) provides both ionic conduction and gas sealing. During the starting-up and operating of MCFC stacks at 923 K, the matrix can experience mechanical stresses that can cause cracking. in particular, the pure alpha-LiAlO2 that is generally used for the MCFC possesses poor mechanical strength. In this study, we employed Al and Li2CO3 particles as reinforcement materials to increase the mechanical strength of the alpha-LiAlO2 matrix for its stable long-term operation. The mechanical strength of the matrix increased dramatically after adding Al particles into the pure matrix. Moreover, we operated a single cell for 2000 h after adding Li2CO3 particles into the Al-reinforced matrix to prevent a Li-ion shortage caused by a lithiated Al reaction in the matrix. (C) 2009 Published by Elsevier Ltd on behalf of Professor T. Nejat Veziroglu.
Keywords: GAMMA-LIALO2 MATRICES; ELECTROLYTE MATRIX; PHASE-STABILITY; LIALO2